Logika Dilema Keamanan Asia Timur dan Rasionalitas Pengembangan Senjata Nuklir Korea Utara - Muhammad Najeri Al Syahrin (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2018)
This article examined how the rationality of nuclear weapons development of North Korea related to the security dilemma. The discussion includes descriptions of chain reactions from the cycle of security dilemmas that create the dynamics of an arms race that threatens the stability of the region's security. The security dilemma for North Korea is characterized by the polarity of forces, historical factors and social construction of amity and enmity. Through the literature study method, the theoretical concepts of security dilemmas serve as the main basis in understanding North Korea's nuclear weapons development. Therefore, this article concluded that the security dilemma in East Asia stems from the fear and threat due to the increasing power and military capability of other countries in the region.